The effectiveness of promotional tools to retain customer loyalty at Kedai Mesra Petronas / Noor Sharyina Samsusah - Samsusah, Noor Sharyina (Faculty of Business and Management, 2009)
This research is all about The Effectiveness of Promotional Tools to Retain Customer Loyalty at Kedai Mesra Petronas. Promotional tools can be the most effective tools that being used by the organization to promote its products or services. This also applied by Petronas to promote their Kedai Mesra. By using the promotional tools medium, Petronas can enhance their customers’ interest towards going to Kedai Mesra. The research objective are: To determine level of customer loyalty at Kedai Mesra Petronas, To rank the factors that influence customer loyalty at Kedai Mesra Petronas, To identify the distribution between promotional tools and customer loyalty at Kedai Mesra Petronas, To recommend the alternative to increase customer loyalty at Kedai Mesra Petronas. In this study, exploratory research was conducted to obtain the information needed. Exploratory research has been chosen because it can define the problem more precisely and give understanding to the researcher. This type of research has been used because of the suitability to identify the level of customer loyalty towards the programs. It involved acquiring primary data, preparing questionnaires and sampling method and deciding on how the variables will be measured. Cronbach’s Alpha for the study is 0.951. In general, reliabilities ranged from 0.9 and 0.99 are considered good. The result of this study indicates that the entire research objective has been achieved. The findings showed that promotion made by Petronas is effective and the most effective tools is the loyalty program and the least effective is advertising towards Kedai Mesra. The researcher also gave some recommendation in order to improve their promotion efforts to be better in the future.